LDMBL: An architecture for reducing code duplication in heavyweight binary instrumentations. (26th June 2018) - Momeni, Behnam; Kharrazi, Mehdi
Summary: Emergence of instrumentation frameworks has vastly contributed to the software engineering practices. As the instrumentation use cases become more complex, complexity of instrumenting programs also increases, leading to a higher risk of software defects, increased development time, and decreased maintainability. In security applications such as symbolic execution and taint analysis, which need to instrument a large number of instruction types, this complexity is prominent. This paper presents an architecture based on the Pin binary instrumentation framework to abstract the low‐level OS and hardware‐dependent implementation details, facilitate code reuse in heavyweight instrumentation use cases, and improve instrumenting program development time. Instructions of x86 and x86‐64 hardware architectures are formally categorized using the Z language based on the Pin framework API. This categorization is used to automate the instrumentation phase on the basis of a configuration list. Furthermore, instrumentation context data such as register data are modeled in an object‐oriented scheme. This makes it possible to focus the instrumenting program development time on writing the essential analysis logics while access to low‐level OS and hardware dependencies are streamlined. The proposed architecture is evaluated by instrumenting 135 instruction types in a concrete symbolic execution engine, resulting in a reduction of the instrumenting program size by 59.7 % . Furthermore, performance overhead measure against the SPEC CINT2006 programs is limited to 8.7 % .